Analysis of conformational, structural, magnetic, and electronic properties related to antioxidant activity : revisiting flavan, anthocyanidin, flavanone, flavonol, isoflavone, flavone, and flavan-3-ol - Farias, Sergio Antônio de Souza (2023)
Arquivo de estruturas utilizadas no estudo publicado. Sem atualizações.